A GM-CSF and CD40L bystander vaccine is effective in a murine breast cancer model - Soliman H (Dove Medical Press, 2015)
Hatem Soliman,1 Melanie Mediavilla-Varela,2 Scott J Antonia,3 1Department of Women's Oncology and Experimental Therapeutics, 2Department of Immunology, 3Department of Thoracic Oncology, Moffitt Cancer Center, Tampa, FL, USA Background: There is increasing interest in using cancer vaccines to treat breast cancer patients in the adjuvant setting to prevent recurrence in high risk situations or in combination with other immunomodulators in the advanced setting. Current peptide vaccines are limited by immunologic compatibility issues, and engineered autologous cellular vaccines are difficult to produce on a large scale. Using standardized bystander cell lines modified to secrete immune stimulating adjuvant substances can greatly enhance the ability to produce immunogenic cellular vaccines using unmodified autologous cells or allogeneic medical grade tumor cell lines as targets. We investigated the efficacy of a cellular vaccine using B78H1 bystander cell lines engineered to secrete granulocyte macrophage-colony stimulating factor and CD40 ligand (BCG) in a murine model of breast cancer. Methods: Five-week-old female BALB/c mice were injected orthotopically in the mammary fat pad with 4T1 tumor cells. Treatment consisted of irradiated 4T1 ± BCG cells given subcutaneously every 4 days and was repeated three times per mouse when tumors became palpable. Tumors were measured two to three times per week for 25 days. The vaccine's activity was confirmed in a second experiment using Lewis lung carcinoma (LLC) cells in C57BL/6 mice to exclude a model specific effect. Interferon-γ (IFN-γ) and interleukin-2 (IL-2) enzyme-linked immunospots (ELISPOTS) were performed on splenic lymphocytes incubated with 4T1 lysates along with immunohistochemistry for CD3 on tumor sections. Results: Tumor growth was significantly inhibited in the 4T1-BCG and LLC-BCG treatment groups when compared to 4T1 and LLC treatment groups. There were higher levels of IL-2 and IFN-γ secreting T-cells on ELISPOT for BCG treated groups, and a trend for higher numbers of tumor infiltrating CD3+ lymphocytes. Some tumors in the 4T1-BCG demonstrated organized lymphoid structures within the tumor microenvironment as well. Conclusion: The use of BCG bystander cell lines demonstrates proof of concept for anti-tumor activity and immunogenicity in an immunocompetent murine model of breast cancer. This vaccine is being evaluated in lung cancer and should be explored further in clinical trials of breast cancer patients at high risk of recurrence or in combination with other immunomodulatory agents. Keywords: breast cancer, immunotherapy, bystander vaccine, CD40L, GM-CSF